The ventral premammillary nucleus at the interface of environmental cues and social behaviors - Cavalcante, Judney Cley; da Silva, Fabiano Gomes; Sáenz de Miera, Cristina; Elias, Carol Fuzeti (Frontiers in Neuroscience, 2025)
The survival of species heavily depends on social behaviors, which in turn rely on the ability to recognize conspecifics within an appropriate environmental context. These behaviors are regulated by the hypothalamus, which processes signals from both the external environment (such as food availability, photoperiod, and chemical cues from other animals) and the internal state (including sex, estrous cycle stage, nutritional status, and levels of stress). Understanding the brain circuits responsible for specific behaviors in experimental animals is a complex task given the intricate interactions between these factors and the diverse behavioral strategies employed by different species. In this review, we will critically evaluate recent studies focused on the ventral premammillary nucleus (PMv) and discuss findings that reveal the PMv as a key, yet sometimes overlooked, node in integrating external and internal environmental cues. We will examine its structural components, internal connectivity, humoral influences, and associated functions, demonstrating the PMv role in the neural regulation of neuroendocrine responses and social behaviors. While much of the existing research centers on rats and mice as model organisms, we will highlight relevant species differences and include a dedicated section for findings in other species.